Preparation method of sodium ion battery negative electrode material with high rate and excellent cycle performance
By sublimating the hydrothermal method of combining sulfur with post-meal waste oil, a sodium ion battery negative electrode material with a wrinkle structure was prepared, which solved the problems of structural changes and low conductivity of existing biomass carbon materials during circulation, and achieved high magnification and excellent cycling performance.
Patent Information
- Application Number
- CN202411898407.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing biomass carbon anode materials are prone to structural changes or fall off during the circulation of sodium ion batteries, resulting in short battery life, low capacity, low electronic conductivity, and poor charging and discharge rates.
Sublimated sulfur and post-meal waste oil are combined, and pre-polycondensation and carbonization are performed by hydrothermal method to obtain a material with a wrinkle structure. This structure increases the contact area between the electrolyte and the carbon negative electrode material, improves the diffusion of sodium ions, reduces the polarization phenomenon of the material, and improves the rate performance.
The high magnification and excellent cycling performance of the negative electrode material of sodium ion battery are achieved, which extends the cycle life of the battery and increases the sodium storage capacity. The preparation method is environmentally friendly and easy to prepare on a large scale.
Smart Images

Figure CN119706791A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion negative electrode materials, and in particular relates to a method for preparing a sodium ion battery negative electrode material with both high rate and excellent cycle performance. Background Art
[0002] The industrial development of sodium-ion batteries is of great significance for alleviating the global energy supply tension and accelerating the energy storage revolution. The working efficiency and capacity of sodium-ion batteries mainly depend on the negative electrode, positive electrode and electrolyte. As one of these components, the negative electrode is an important part of the sodium-ion battery. Due to its characteristics and structure, the negative electrode has a huge impact on the overall performance of the battery. Carbon materials have the advantages of wide sources, low cost, excellent conductivity, good cycle stability, high sodium storage capacity and environmental friendliness, and are regarded as a promising negative electrode material.
[0003] At present, the research and development of carbon materials is mainly focused on biomass carbon materials. Biomass carbon precursors mainly refer to the roots, stems and leaves of plants (for example: banana peels, peat moss, peanut shells, leaves, apple peels, grapefruit peels, poplar and cotton, etc.). However, due to regional differences, the structure of the subsequent carbonized materials of such biomass carbon material precursors is quite different, and it is difficult to directly apply them to the field of negative electrode materials. Post-meal waste oil is a waste oil, and its main component is triglyceride. It has the advantages of low cost, wide source, easy storage and not easy to deteriorate. Using it to develop negative electrode materials for sodium ion batteries will not only have broad commercial prospects, but also its reuse is in line with the concept of sustainable development.
[0004] However, when biomass carbon negative electrode materials are directly applied to secondary batteries, structural changes or active material shedding may occur during the battery's charge and discharge cycle, resulting in a reduced battery cycle life. At the same time, the electronic conductivity of biomass carbon negative electrode materials is relatively low, which leads to poor battery charge and discharge rates and reduced capacity.
[0005] In order to improve the problems of short battery life and low capacity, such problems can be improved through synthesis methods such as heteroatom doping and material structure engineering. However, in such heteroatom-doped biomass carbon materials, it is still a huge challenge to achieve low-cost and reasonable utilization of materials, higher theoretical electrochemical capacity, and effective bonding between heteroatoms and carbon atoms to form sufficient sodium ion storage active sites. In addition, the synthesis process of oil materials requires the use of auxiliary reagents such as curing agents to increase the carbon yield, and the complex process and high cost hinder its application. Therefore, waste oil is first pre-condensed through a hydrothermal reaction to increase its molecular weight. In addition, a certain amount of heteroatoms are bonded to the carbon atoms in the material through a simple synthetic route, which not only improves the carbon yield of the material, but also effectively increases the carbon layer spacing of the material, improves the electrochemical performance, and realizes the reuse of waste oil, which has certain practical application value. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a negative electrode material for a sodium ion battery having both high rate and excellent cycle performance, wherein sublimated sulfur is combined with postprandial waste oil, and a material having a wrinkled structure is obtained by hydrothermal method, pre-condensation and carbonization treatment. This structure can effectively increase the contact area between the electrolyte and the carbon negative electrode material, facilitate the diffusion of sodium ions in the material, and then weaken the polarization phenomenon of the material as a sodium ion negative electrode material, thereby improving the rate performance of the material. In addition, the aliphatic hydrocarbons in the postprandial waste oil are pre-condensed by hydrothermal treatment of the postprandial waste oil and sublimated sulfur, effectively improving the problem of low yield of direct carbonization treatment of the postprandial waste oil material.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A method for preparing a negative electrode material for a sodium ion battery having both high rate and excellent cycle performance comprises the following steps:
[0009] 1) 1-6 g of sublimated sulfur is added to 5-20 g of post-meal waste oil and stirred magnetically for 0.5-3 h to form a viscous mixture;
[0010] 2) The viscous mixture is placed in a polytetrafluoroethylene container and reacted in a high pressure reactor at 150-200° C. for 6-16 hours, and then cooled to room temperature after the reaction is completed;
[0011] 3) the sample cooled to room temperature in step 2) is heated to 300-500° C. at 2-5° C. / min in a tube furnace under an inert atmosphere, and kept at a constant temperature for 0.5-3 h, and then cooled to room temperature;
[0012] 4) The sample obtained in step 3) is heated to 600-1000° C. at 2-5° C. / min in a tube furnace under an inert atmosphere, and kept at a constant temperature for 0.5-3 h, and cooled to obtain a negative electrode material for a sodium ion battery.
[0013] The post-meal waste oil is the waste oil from restaurants after meals, and the waste oil is the waste oil from which food residues have been removed.
[0014] The product obtained in step 2) is a viscous mixture.
[0015] The inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0016] The sodium ion battery negative electrode material obtained in step 4) is assembled into a sodium ion half-cell, which has a maximum reversible capacity of 330-390 mAh / g at a current density of 0.1 A / g; after 500 cycles at a current density of 1 A / g, it has a discharge specific capacity of 176.8 mAh / g, and after 1000 cycles, it has a discharge specific capacity of about 155 mAh / g, and a capacity retention rate of 75%-78%.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention combines sublimated sulfur with post-meal waste oil, and obtains a material with a wrinkled structure through a hydrothermal method, pre-condensation and carbonization treatment. This structure can effectively increase the contact area between the electrolyte and the carbon negative electrode material, facilitate the diffusion of sodium ions in the material, and then weaken the polarization phenomenon of the material as a sodium ion negative electrode material, thereby improving the rate performance of the material. In addition, the aliphatic hydrocarbons in the post-meal waste oil are pre-condensed by hydrothermal treatment of the post-meal waste oil and sublimated sulfur, which effectively improves the problem of low yield of direct carbonization treatment of the post-meal waste oil material; secondly, sublimated sulfur is doped into the carbon material as a heteroatom, which expands the carbon layer spacing and increases the sodium ion storage site, thereby improving the sodium storage capacity of the material. This preparation method is environmentally friendly and easy to prepare on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a flow chart for the preparation of negative electrode materials for sodium ion batteries.
[0020] Figure 2 This is the XRD diagram of WCO@S73-700 negative electrode material.
[0021] Figure 3 Middle: (a), (b), and (c) are SEM images of WCO@S73-700 negative electrode materials at different magnifications.
[0022] Figure 4 Middle: (a) is the full XPS spectrum of WCO@S73-700 material;
[0023] (b) is the C1s fine spectrum of WCO@S73-700 material;
[0024] (c) is the S2p fine spectrum of WCO@S73-700 material.
[0025] Figure 5 This is the cycle performance diagram of the WCO@S73-700 negative electrode material after 100 cycles at a current density of 0.1A / g.
[0026] Figure 6 This is the cycle performance diagram of the WCO@S73-700 negative electrode material after 1000 cycles at a current density of 1A / g.
[0027] Figure 7 This is the rate performance diagram of WCO@S73-700 negative electrode material at different current densities.
[0028] Figure 8 This is the impedance spectrum of WCO@S73-700 negative electrode material.
[0029] Fig. 9 This is the XRD diagram of WCO@S73-600 negative electrode material.
[0030] Fig.10 This is the cycle performance diagram of the WCO@S73-600 negative electrode material after 100 cycles at a current density of 0.1A / g.
[0031] Fig.11 This is the cycle performance diagram of the WCO@S73-600 negative electrode material after 1000 cycles at a current density of 1A / g.
[0032] Fig.12 This is the rate performance diagram of WCO@S73-600 negative electrode material at different current densities.
[0033] Fig.13 This is the XRD diagram of WCO@S73-800 negative electrode material.
[0034] Fig.14 This is the cycle performance diagram of the WCO@S73-800 negative electrode material after 100 cycles at a current density of 0.1A / g.
[0035] Fig.15 This is the cycle performance diagram of the WCO@S73-800 negative electrode material after 1000 cycles at a current density of 1A / g.
[0036] Fig.16 This is the rate performance diagram of WCO@S73-800 negative electrode material at different current densities. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0038] Example 1
[0039] See Figure 1 A method for preparing a WCO@S-700 material having both excellent cycle and high rate performance comprises the following steps:
[0040] 1) Take 6 g of sublimated sulfur and add it to 14 g of post-meal waste oil (food residues have been filtered out), and stir it magnetically at room temperature for 3 hours until there is no solid particulate matter, forming a viscous mixture.
[0041] 2) The obtained mixture was transferred into a 100 ml polytetrafluoroethylene container and reacted in a high-pressure reactor at 180° C. for 12 h. After the reaction was complete, the high-pressure reactor was allowed to cool naturally to room temperature.
[0042] 3) The sample cooled to room temperature was heated to 350°C at 3°C / min in a tube furnace under a nitrogen atmosphere, and kept at a constant temperature at 350°C for 2 hours. After cooling to room temperature, the sample was heated to 700°C at 3°C / min in a tube furnace under a nitrogen atmosphere, and kept at a constant temperature at 700°C for 2 hours to obtain WCO@S-700 material.
[0043] Depend on Figure 2 It can be seen that the WCO@S73-700 material has two diffraction peaks at approximately 23° and 43°, corresponding to the (002) and (101) crystal planes of typical amorphous carbon, respectively, and the peaks of the diffraction peaks are relatively broad, which indicates that the crystallites of the material are amorphous structures.
[0044] from Figure 3 As can be seen in (a) and (b), WCO@S73-700 is made of a stack of wrinkled lamellar carbon materials. A large number of irregular pore structures are formed between the layers. As can be further seen in (c), the thickness of this thin lamellar structure is 300-800nm, which is beneficial to improving the transmission performance of sodium ions. This irregular pore structure and lamellar structure are conducive to the infiltration of the electrolyte, achieving full contact between the electrolyte and the main material.
[0045] See Figure 4 From the full spectrum of (a), we can see that there are C (284.8 eV), O (531.3 eV) and S (S2s 229.3 eV, S2p 165.1 eV) elements in WCO@S73-700 material. Figure 4In (b), four main characteristic peaks can be observed at 284.7eV, 285.1eV, 286.4eV and 289.9eV in the C1s fine spectrum, which are respectively attributed to CC / C=C, CS, CO and C=O bonds, indicating that S atoms have been successfully doped into the carbon matrix. Figure 4 In (c), there are two strong peaks in the HRXPS spectrum of S2p, located at 163.9 and 165.1 eV, corresponding to the S2p of CSC covalent bond. 3 / 2 and S2p 1 / 2 The characteristic peak of the orbital, the peak at 167.2 eV corresponds to SO x These sulfur configurations can store sodium active sites, thereby improving the overall electrochemical performance of the material.
[0046] Depend on Figure 5 It can be seen that when the current density of WCO@S73-700 material is 0.1A / g, it still has a reversible capacity of 389.8mAh / g after 100 cycles.
[0047] Depend on Figure 6 It can be seen that the WCO@S73-700 electrode material has a reversible capacity of 176.8 mAh / g after 500 cycles at 1 A / g, and still has a reversible capacity of 155.2 mAh / g after 1000 cycles, with a capacity retention rate of 74.16%.
[0048] Depend on Figure 7 It can be seen that the capacity of WCO@S73-700 electrode material is 326.4mAh / g, 310.2mAh / g, 283.9mAh / g, 254.7mAh / g, 213mAh / g and 159.4mAh / g at current densities of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g and 5A / g, respectively. And when the current density is increased from 5A / g and returned to 0.1A / g, the capacity does not decrease significantly compared with the just-discharged state, indicating that the material has excellent rate performance, which is due to its good conductivity.
[0049] Depend on Figure 8 It can be seen that the charge transfer impedance of the WCO@S73-700 electrode material is 27.9Ω, which shows that the WCO@S73-700 electrode material has very excellent conductive properties.
[0050] Example 2
[0051] A method for preparing a WCO@S-600 material having both excellent cycle and high rate performance comprises the following steps:
[0052] 1) 6 g of sublimated sulfur was added to 14 g of post-meal waste oil, and magnetically stirred at room temperature for 3 h until no solid particles were present, forming a viscous fluid.
[0053] 2) The obtained fluid was transferred into a 100 ml polytetrafluoroethylene container and reacted in a high-pressure reactor at 180° C. for 12 h. After the reaction was complete, the high-pressure reactor was allowed to cool naturally to room temperature.
[0054] 3) The sample cooled to room temperature was heated to 350°C at 3°C / min in a tube furnace under a nitrogen atmosphere, and kept at 350°C for 2 h. After cooling to room temperature, the sample was heated to 600°C at 3°C / min in a tube furnace under a nitrogen atmosphere, and kept at 600°C for 2 h.
[0055] Depend on Fig. 9 It can be seen that the WCO@S73-600 material has two diffraction peaks at approximately 23° and 43°, corresponding to the (002) and (101) crystal planes of typical amorphous carbon, respectively, and the peaks of the diffraction peaks are relatively broad, which indicates that the crystallites of the material are amorphous structures.
[0056] Depend on Fig.10 It can be seen that when the current density of WCO@S73-600 material is 0.1A / g, it still has a reversible capacity of 266.8mAh / g after 100 cycles.
[0057] Depend on Fig.11 It can be seen that the WCO@S73-600 electrode material has a reversible capacity of 169.6 mAh / g after 500 cycles at 1 A / g, and still has a reversible capacity of 173.5 mAh / g after 1000 cycles, with a capacity retention rate of 79.8%.
[0058] Depend on Fig.12 It can be seen that the capacity of WCO@S73-600 electrode material is 124.3mAh / g, 93.9mAh / g, 68.6mAh / g, 49.4mAh / g, 29.7mAh / g and 23.5mAh / g at current density of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g and 5A / g respectively. And when the current density increases to 5A / g and returns to 0.1A / g, the capacity does not decrease significantly compared with the just-discharged state, indicating that the material has excellent rate performance, which is due to its good conductivity.
[0059] Example 3
[0060] A method for preparing a WCO@S-800 material having both excellent cycle and high rate performance comprises the following steps:
[0061] 1) 6 g of sublimated sulfur was added to 14 g of post-meal waste oil, and magnetically stirred at room temperature for 3 h until no solid particles were present, forming a viscous fluid.
[0062] 2) The obtained fluid was transferred into a 100 ml polytetrafluoroethylene container and reacted in a high-pressure reactor at 180° C. for 12 h. After the reaction was complete, the high-pressure reactor was allowed to cool naturally to room temperature.
[0063] 3) The sample cooled to room temperature was heated to 350°C at 3°C / min in a tube furnace under a nitrogen atmosphere, and kept at 350°C for 2 h. After cooling to room temperature, the sample was heated to 800°C at 3°C / min in a tube furnace under a nitrogen atmosphere, and kept at 800°C for 2 h.
[0064] Depend on Fig.13 It can be seen that the WCO@S73-800 material has two diffraction peaks at approximately 23° and 43°, corresponding to the (002) and (101) crystal planes of typical amorphous carbon, respectively, and the peaks of the diffraction peaks are relatively broad, which indicates that the crystallites of the material are amorphous structures.
[0065] Depend on Fig.14 It can be seen that when the current density of WCO@S73-800 material is 0.1A / g, it still has a reversible capacity of 194.4mAh / g after 100 cycles.
[0066] Depend on Fig.15 It can be seen that the WCO@S73-600 electrode material has a reversible capacity of 163.2 mAh / g after 500 cycles at 1 A / g, and still has a reversible capacity of 154.9 mAh / g after 1000 cycles.
[0067] Depend on Fig.16 It can be seen that the capacity of WCO@S73-800 electrode material is 229.8mAh / g, 199.2mAh / g, 174mAh / g, 155.1mAh / g, 134.9mAh / g and 133.7mAh / g at current density of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g and 5A / g respectively. And when the current density increases to 5A / g and returns to 0.1A / g, the capacity does not decrease significantly compared with the just-discharged state, indicating that the material has excellent rate performance, which is due to its good conductivity.
[0068] The present invention combines sublimated sulfur with post-meal waste oil, and obtains a material with a wrinkled structure through a hydrothermal method, pre-condensation and carbonization treatment. This structure can effectively increase the contact area between the electrolyte and the main material, facilitate the diffusion of sodium ions in the material, and then weaken the polarization phenomenon of the material as a sodium ion negative electrode material, thereby improving the rate performance of the material. In addition, the aliphatic hydrocarbons in the post-meal waste oil can be pre-condensed by hydrothermal treatment of the post-meal waste oil and sublimated sulfur, which effectively improves the problem of low yield of direct carbonization treatment of the post-meal waste oil material; secondly, sublimated sulfur is doped into the carbon material as a heteroatom, which expands the carbon layer spacing and increases the sodium ion storage site, thereby improving the sodium storage capacity of the material. This preparation method is environmentally friendly and easy to prepare on a large scale.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery having both high rate and excellent cycle performance, characterized in that: The following steps are involved: 1) 1-6 g of sublimated sulfur is added to 5-20 g of post-meal waste oil and stirred magnetically for 0.5-3 h to form a viscous mixture; 2) The viscous mixture is placed in a polytetrafluoroethylene container and reacted in a high pressure reactor at 150-200° C. for 6-16 hours, and then cooled to room temperature after the reaction is completed; 3) the sample cooled to room temperature in step 2) is heated to 300-500° C. at 2-5° C. / min in a tube furnace under an inert atmosphere, and kept at a constant temperature for 0.5-3 h, and then cooled to room temperature; 4) The sample obtained in step 3) is heated to 600-1000° C. at 2-5° C. / min in a tube furnace under an inert atmosphere, and kept at a constant temperature for 0.5-3 h, and cooled to obtain a negative electrode material for a sodium ion battery.
2. The method for preparing a negative electrode material for a sodium ion battery having both high rate and excellent cycle performance according to claim 1, characterized in that: The post-meal waste oil is the waste oil from restaurants after meals, and the waste oil is the waste oil from which food residues have been removed.
3. The method for preparing a negative electrode material for a sodium ion battery having both high rate and excellent cycle performance according to claim 1, characterized in that: The product obtained in step 2) is a viscous mixture.
4. The method for preparing a negative electrode material for a sodium ion battery having both high rate and excellent cycle performance according to claim 1, characterized in that: The inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
5. According to the method for preparing a sodium ion battery negative electrode material with high rate and excellent cycle performance according to claim 1, the sodium ion battery negative electrode material obtained in step 4) is assembled into a sodium ion half-cell, and the sodium ion half-cell has a maximum reversible capacity of 330-390 mAh / g at a current density of 0.1 A / g; after 500 cycles at a current density of 1 A / g, it has a discharge specific capacity of 176.8 mAh / g, and after 1000 cycles, it has a discharge specific capacity of about 155 mAh / g, and the capacity retention rate is 75%-78%.